2007
DOI: 10.1002/pts.785
|View full text |Cite
|
Sign up to set email alerts
|

Fact or friction: a model for understanding the openability of wide mouth closures

Abstract: Understanding and improving openability is becoming more and more important in the packaging industry. Specific tests or focus groups can be used to determine whether users have problems with packaging; however, these are both time consuming and expensive. This paper outlines a method by which it is possible to predict openability for any kind of closure by utilizing simple and quick tests, and by mathematically adapting strength test data. The method is demonstrated on wide mouth closures, and shows that ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 15 publications
0
39
0
Order By: Relevance
“…There may well be situations where reducing a grip spacing results in a subject being able to apply less force or torque to a product. For example, studies 9 have shown that in the case of vacuum lug closures, users can apply the highest level of torque to 73-mm-diameter lids. This was found to be the optimum value for both male and female users and although no specific hand measurements were made, a wide age range of subjects was used, suggesting that this optimum value may be independent of hand size.…”
Section: Discussionmentioning
confidence: 98%
“…There may well be situations where reducing a grip spacing results in a subject being able to apply less force or torque to a product. For example, studies 9 have shown that in the case of vacuum lug closures, users can apply the highest level of torque to 73-mm-diameter lids. This was found to be the optimum value for both male and female users and although no specific hand measurements were made, a wide age range of subjects was used, suggesting that this optimum value may be independent of hand size.…”
Section: Discussionmentioning
confidence: 98%
“…6,7 Much of the research into designing food packaging which is 'user-friendly' for an ageing population has involved measuring wrist strength for twisting jar lids. [8][9][10][11][12][13][14][15][16][17] This information is valuable for ensuring that jars are designed with the ageing consumer in mind. However, it does not provide any indication for what the ageing consumers actually look for when purchasing food in packages and their attitudes towards currently available packaging.…”
Section: Introductionmentioning
confidence: 98%
“…Further details of the methods used to determine required opening torque can be found in the author's previous paper. 7 …”
Section: Methodsmentioning
confidence: 97%